In vitro Study on the Effect of Smoking and Alcohol on the Proliferation of Oral Cancer Cells - Ashutosh Panda; Neha Gupta; Usha Balan; Hiren H. Patadiya; Sushil K. Sahoo; Manish Kumar; Naina Pattnaik; Mahesh Ghadage (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Smoking and alcohol use are major risk factors for oral cancer, one of the most common diseases in the world. To better understand their involvement in tumor development, this in vitro research assesses the individual and combined effects of alcohol and smoking on the growth of oral cancer cells. Materials and Methods: Under normal circumstances, a human oral squamous cell carcinoma cell line (SCC-25) was cultivated. The cells were treated with ethanol (1%, 5%, and 10%) to mimic alcohol intake and nicotine (10 μM, 20 μM) to mimic smoking. Additionally, a combination of the two drugs was explored. The MTT test was used to measure cell growth at 24, 48, and 72 hours. One hundred percent proliferation was chosen as the arbitrary control value. Phase-contrast microscopy was used to assess morphological changes. Results: Ethanol at 10% enhanced cell proliferation by 25% at 48 hours (P < 0.05), whereas nicotine at 20 μM boosted cell proliferation by 30% at 72 hours compared to control (P < 0.05). At 72 hours, there was a 50% increase in proliferation (P < 0.01) due to the synergistic action of 20 μM nicotine and 10% ethanol. Significant morphological alterations, including increased cellular spreading and clumping, which are suggestive of aggressive behavior, were seen in cells treated to the mixture using phase-contrast microscopy. Conclusion: This in vitro research shows that drinking and smoking both separately and together promote the growth of oral cancer cells. These results highlight the need for public health initiatives to lower these risk factors and recommend further research to examine the biological processes behind them.